Effect of Different Levels of Protein and Protexin on Broiler Performance - Mehr, M. Azadegan; Shargh, M. Shams; Dastar, B.; Hassani, S.; Akbari, M.R. (International Journal of Poultry Science, 2007)
A feeding trail was conducted to evaluate the effects of different levels of dietary protein and protexin (a commercial probiotic compound) on broiler performance. In a completely randomized design with 2 x 3 factorial arrangement, 360 male broiler chicks were divided into 24 groups, 15 chicks per. Treatments consisted of combination of two levels of protein (NRC and 90% of NRC) and three levels of protexin (without protexin, the recommended level and 120% of recommended level). All of the diets were formulated according to the NRC tables except for protein. Protexin significantly (P